Pedagogical professional performance of teachers in the "Hermanos Saíz Montes de Oca" Mixed Center - Yanisleidy Cruz Melgarejo; Armando Acosta Iglesias; Aimara Álvarez Cabreriza (Revista MENDIVE, 2023)
The expansion of the mixed centers in the National Education System in Cuba is part of the transformations that have been carried out since the 2010-2011 school year, and currently they have been expanded with greater. In these institutions, several educational levels are combined with a single direction, which must favor the system of educational influences. At the "Hermanos Saíz Montes de Oca" Joint Center in the municipality of San Luis in Pinar del Río, students from Basic Secondary and Technical and Professional Education converge, which demands renewed and innovative actions from teachers to face the challenges of the activity. Educational; that is, a professional pedagogical performance according to such demands. It is important to point out that Technical and Professional Education is a different education; distinctive for its peculiarities. The objective of this work was to socialize a pedagogical strategy that contributes to the improvement of the professional pedagogical performance of teachers in the aforementioned institution. The research was carried out on a dialectical-materialistic basis, in which theoretical and empirical methods were used, such as historical-logical, inductive-deductive, analysis-synthesis, modeling, system approach, observation, analysis documentary and interview, which allowed a theoretical and practical study of the educational reality to arrive at this scientific result, which contributed to the professional pedagogical performance of teachers in their educational practice.